1988
DOI: 10.1051/rnd:19881010
|View full text |Cite
|
Sign up to set email alerts
|

Protéines trophoblastiques

Abstract: Summary. Trophoblastic proteins.Many studies conducted on human or animal placenta (chorion)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several proteins have been identified at later stages of pregnancy Beckers et al, 1988;Godkin et al, 1988;Martal et al, 1988). Among those, PSPB (pregnancy-specific protein ) has been isolated from cattle embryos at Day 24 to Day 40 (Butler et al, 1982) and found in the peripheral circulation of some pregnant animals as early as Day 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins have been identified at later stages of pregnancy Beckers et al, 1988;Godkin et al, 1988;Martal et al, 1988). Among those, PSPB (pregnancy-specific protein ) has been isolated from cattle embryos at Day 24 to Day 40 (Butler et al, 1982) and found in the peripheral circulation of some pregnant animals as early as Day 20 .…”
Section: Introductionmentioning
confidence: 99%